Converting Digital Capital in Five Key Life Realms - Ragnedda, Massimo; Ruiu, Maria Laura; Addeo, Felice; Delli Paoli, Angela (Italian Sociological Review, 2022)
This article theorizes fresh connections between Bourdieusian social theory, and the digital divide in five key areas: political, economic, cultural, social, and personal digital advantage. In so doing it makes new arguments about how digital resources result in benefits that accrue from the combination of both access to and use of ICTs. In this way, the findings shed additional light on the third level of the digital divide by focusing on the role played by digital capital in influencing the uneven distribution of benefits that derive from the use of the Internet. Based on a structured sample of the UK population, the article adopts the model of digital capital developed by Ragnedda, Ruiu and Addeo (2019). Findings show that varied levels of digital capital are related to engagement in activities that have political, social, economic, cultural, and personal valence. Thus, the study offers compelling evidence of the increasing importance of digital capital in everyday life.